2004
DOI: 10.1093/molbev/msh186
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Female and Male Lineages in Sub-Saharan Populations: the Importance of Sociocultural Factors

Abstract: In this paper, we present a study of genetic variation in sub-Saharan Africa, which is based on published and unpublished data on fast-evolving (hypervariable region 1 of mitochondrial DNA and six microsatellites of Y chromosome) and slow-evolving (haplogroup frequencies) polymorphisms of mtDNA and Y chromosome. Our study reveals a striking difference in the genetic structure of food-producer (Bantu and Sudanic speakers) and hunter-gatherer populations (Pygmies, Kung, and Hadza). In fact, the ratio of mtDNA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
105
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 40 publications
17
105
2
1
Order By: Relevance
“…AGR-to-RHG admixture rate estimates were thus on average 8.8 times larger than RHG-to-AGR estimates, supporting the occurrence of asymmetrical admixture from AGR to RHG populations. Furthermore, our comparison of ancestry proportions on the X chromosome and the autosomes in AGR and some RHG populations, and a large body of studies based on uniparentally inherited markers 18,38,39 , suggest that during the admixture process there has been preferential mating of AGR males with RHG females (Supplementary Note 2, Supplementary Fig. 7, Supplementary Tables 5 and 6).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…AGR-to-RHG admixture rate estimates were thus on average 8.8 times larger than RHG-to-AGR estimates, supporting the occurrence of asymmetrical admixture from AGR to RHG populations. Furthermore, our comparison of ancestry proportions on the X chromosome and the autosomes in AGR and some RHG populations, and a large body of studies based on uniparentally inherited markers 18,38,39 , suggest that during the admixture process there has been preferential mating of AGR males with RHG females (Supplementary Note 2, Supplementary Fig. 7, Supplementary Tables 5 and 6).…”
Section: Resultsmentioning
confidence: 82%
“…First, we show that the bulk of the admixture between various groups of RHG and neighbouring AGR took place only recently, within the past B1,000 years. This indicates that the earliest phase of the diffusion of an agriculturebased lifestyle, where an avant-garde of farming communities in the Western (c. 3,000-5,000 YBP) and Eastern (c. 2,500-3,000 YBP) equatorial rainforest 3,6,15,54 promoted early socio-economic and cultural interactions with local RHG 2,3,7,8,11,[15][16][17][18][19] , was not accompanied by immediate, extensive genetic exchanges. Our results suggest instead that admixture started extensively at a later stage, well after the introduction of iron tools and plant cultivation and the subsequent rise of territorial chiefdoms, profoundly transforming the interactions between the two communities 15,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[31][32][33] The data set includes 39 populations from the major language groups: Khoisan (!Kung1, !Kung2, Khwe, Hadza), Nilo-Saharan (Kanuri, Songhai, Turkana, Nubian, Sudanese, Mbuti, Datoga), Afroasiatic (Moroccan Berber, non-Berber Moroccan, Egyptian, Algerian Mozabite, Tuareg, Somalian, Amhara, Hausa, Podokwo, Mandara, Uldeme, Iraqw), Niger-Congo non-Bantu (Fulbe ¼ Fulfulde, Yoruba, Serer, Wolof, Mandinka, Tupuri), and Niger-Congo Bantu (Bubi, Fang, Biaka, Kikuyu, Mozambique1, Mozambique2, Bakaka, Bassa, Mbenzele, Sukuma) ( Figure 1). Some populations represented in the original data sets 12,31 -33 were omitted because they are not found on the African mainland, are Cameroonian populations not represented in the Y chromosome data set, 33 or because linguistic designations could not be inferred.…”
Section: Mtdnamentioning
confidence: 99%
“…The approximate location of 40 populations typed for Y chromosome markers in this study (K) and 39 populations surveyed for HVS1 sequence data 12,31,32,33 (J) are indicated. The distribution of the four African language families was constructed using Greenberg's 39 classifications and further refined with data from the ethnologue (http://www.ethnologue.com/).…”
Section: Mantel Testsmentioning
confidence: 99%